A Rebalancing China and Resurging India : How Will the Pendulum Swing for Russia? - Sanghi, Apurva (Alex Publishers, 2017)
This report assesses the future impact of two dynamically transforming economies – China and India – on Russia’s economy. China is slowing down and rebalancing its economy whereas India is rapidly expanding. What does this hold for Russia? The report begins with a snapshot of findings, followed by eight chapters. Chapter one motivates the topic and identifies analytical and empirical gaps that this report fills. Chapter two examines the current pattern of trade between Russia and the two countries, and it discusses how important – or not – China and India’s economies are for Russia. Chapter three follows by summarizing the results of three complementary approaches for measuring Russia’s trade potential with China and India (and also the rest of the world). Chapter fourth intuitively describes the customized methodology developed for this report; its major caveats and assumptions, and its possible extensions (technical details, for those interested, are in the annexes). Chapter fifth outlines four plausible scenarios of the potential impact on Russia of changes in China and India, and chapter sixth presents the results. Chapter seventh explores the sensitivity of results to changes key in assumptions. Finally, chapter eighth concludes with emerging policy implications for Russia.